Analisis Pemikiran Harald Motzki Tentang Hadis – Hadis Hukum: Metodologi Isnad Cum Matn dan Implikasinya Pada Studi Otorisitas Hadis: Analysis of Harald Motzki’s Thoughts on Legal Hadiths: Isnad Cum Matn Methodology and its Implications for the Study of the Authority of Hadith - M Faza Nahri (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2026)
The study of hadith in the discourse of modern Islamic studies is often caught between the polarity of traditionalism that accepts narrations without criticism and the radical skepticism of classical orientalists who doubt their historicity. This study aims to analyze the isnād-cum-matn analysis (ICMA) methodology developed by Harald Motzki in studying legal hadith and examine its implications for the authority of hadith in contemporary Islamic studies. The methodology used is qualitative research with a library research model and content analysis of Motzki's main works and other supporting literature. The results show that Motzki's approach offers a "middle way" position that systematically revises the skeptical paradigms of Joseph Schacht and Ignaz Goldziher. Through an in-depth analysis of early collections such as Muṣannaf ‘Abd al-Razzāq al-Ṣan‘ānī, Motzki successfully proves that a number of legal hadith have historical roots that can be traced back to the first century of the Hijriah and are connected to the generation of the Companions. This research's contribution lies in strengthening the methodological foundations of hadith science by integrating empirical criticism of the sanad and matan (transmitted texts), while simultaneously restoring the historical legitimacy of hadith as a fundamental source in the formation of Islamic law. Thus, ICMA is a crucial instrument in bridging the gap between Western academic tradition and classical hadith methodology, thereby strengthening the authority of hadith in the contemporary era.